Higher-Dimensional Anisotropic Modified Holographic Ricci Dark Energy Cosmological Model in Lyra Manifold - Das, K.; Bharali, J. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We used modified holographic Ricci dark energy to find anisotropic LRS Bianchi type I cosmological model in five-dimensions based on Lyra geometry. The exact solutions of the Einstein field equations were obtained by using hybrid expansion law (HEL). We have investigated the interacting and non-interacting dark energy and dark matter. It is found that at late times the equation of state parameter (EOS) for non-interacting case behaves like a cosmological constant whereas it behaves like phantom dark energy for interacting model. Some cosmological parameters and stability of the models are discussed. The physical and geometric aspects of the models have been analysed. They are consistent with the recent observational results. Чтобы найти анизотропную космологическую модель LRS Бьянки типа I в пяти измерениях на основе геометрии Лиры, использована модифицированная голографическая темная энергия Риччи. Точные решения уравнений поля Эйнштейна получены с помощью гибридного закона расширения (HEL). Задача рассмотрена как при наличии взаимодействия между темной энергией и темной материей, так и при ее отсутствии. Обнаружено, что на поздних стадиях расширения уравнение параметра состояния (EOS) для невзаимодействующего случая ведет себя как космологическая постоянная, тогда как для взаимодействующей модели оно ведет себя как фантомная темная энергия. Обсуждаются некоторые космологические параметры и устойчивость моделей.
Keywords: Astrophysics